If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2h-2=16
We move all terms to the left:
2h-2-(16)=0
We add all the numbers together, and all the variables
2h-18=0
We move all terms containing h to the left, all other terms to the right
2h=18
h=18/2
h=9
| 2(3x-1)=5x-5 | | 3^x+3-3^x+1=24 | | x(x+3)+5(x+3)=x+3x+5x+15 | | 2x+3*2^(x+1)=28 | | 2x+3*2^x+1=28 | | 7-2xx=-3 | | 5m-1=9 | | -10(s+5)=-72 | | –6+x=–3 | | _m-÷3=4 | | -6(3w-3)+2w=2(w+8) | | 2-x=9+2x | | -4(4x-2)+4x=9+3(2x-3) | | 3(2x+4)+2=-5x+25 | | 12-1,28(x-5)=22-2(x+4) | | 1+x/2-1/2-x/4+1/4=x/3+3/3 | | 3t+4=t13 | | 2x/4=x+3/3 | | 3x²=4x | | X²=2x | | 3z/10-4=3 | | (q-10)5=32 | | 5(q-10)=32 | | 4(e+5)=32 | | (x+6)(x-6)=10x+x*x-2*x*4+4*4 | | 2(x-2)+8=-2x+44 | | (3x+1)/4+(5x-2)/3=7 | | (4x)/(x+3)+12/(5x−3)=161/((5x−3)(x+3)) | | 4x^2-24+36=0 | | n/3+0.4=1 | | 4+y=–3 | | 3(2x+4)=4x-8 |